Identification of Contrast Induced Nephropathy (CIN) with intravenous iso-Osmolar contrast media in renal failure patients with and without additional comorbidities undergoing Computed Tomography - Thomas Mathew; Prakashini K; Rahul P Kotian (International Journal of Medical Research and Review, 2016)
Aim: To identify contrast induced nephropathy with intravenous iso-osmolar contrast media in renal failure patients with additional comorbidities undergoing computed tomography.Study design: Hospital based observational study.Methods: A retrospective study was conducted on 207 patients with pre-existing renal failure and comorbidities. In this study we collected pre-contrast creatinine values available within 3 weeks and post-contrast creatinine value was collected on 2nd and 5th day following CM injection in order to check early and late contrast induced nephropathy (CIN). Rate of CIN with and without comorbid conditions in CKD patients were calculated. Then we assessed the incidence of CIN with different amount of CM administered. We also calculated the relation of CIN with pre-contrast creatinine and eGFR range, which was categorized as 1.4- 2.0 mg/dL, 2.0-3.0 mg/dL and >3 mg/dL and >60ml and <60 mL/min per 1.73 m2 respectively.Results: Rate of CIN was relatively higher in renal failure patients and also in patients with comorbidities especially diabetes mellitus. Risk of CIN development was possible on 5th day also which was considered as delayed CIN. It was shown in the study that as the amount of contras media increases, rate of CIN also increases which was prominent in case of patients administered with >80ml of contrast media. CIN risk was better determined by eGFR than Creatinine value.Conclusion: CIN rate was clinically significant in CKD patients with comorbidities who received an iso-osmolar contrast media.